Detection of visuomotor dysfunction in mild traumatic brain injury using binocular retinal polarization scanning - Shoshany, Talia N; Torres-Quinones, Carlos; Silverman, Erika; Shaka, Justin; Diaz-Arrastia, Ramon; Goldstein, Lee; Hunter, David G (Brain injury, 2023)
The head and intraocular trauma tool (HITT) is a portable, binocular retinal polarization scanner (RPS) that detects ocular fixation with high precision to assess visuomotor function. We conducted a pilot evaluation of a prototype binocular RPS device to evaluate alterations in fixation stability, binocularity (convergence), and saccadic latency after mild traumatic brain injury (mTBI). Two groups were studied prospectively: (1) single observation study of mTBI patients in a hospital ER ( = 7) and age-matched controls ( = 43); (2) high-school athletes preseason ( = 28), after sports-related mTBI ( = 3), and at season end ( = 5). Subjects were asked to fixate on an internal target and track randomly presented peripheral and central targets as fixation was assessed using binocular RPS. There were clinically and statistically significant alterations in the hospital ER group after mTBI, including a decrease in fixation stability (54.6% in patents vs 90.2% in controls, = 0.014) and binocularity (28.7% in patients vs 86.6% in controls; = 0.004). Similar trends, not statistically significant, were observed in saccadic latency in the hospital ER group as well as in the injured high school athletes. The HITT device shows promise as an objective, noninvasive method for assessment of the impact of mTBI on visuomotor function. Additional studies with larger patient populations are required to evaluate efficacy for clinical use.